A sliver of light ebook Three americans imprisoned in iran. - Bauer, Shane (2014)
Hikers held captive in Tehran tell their story in “a moving memoir by three individuals who found the strength to survive” ( San Jose Mercury News ).   During the summer of 2009, Shane Bauer, Joshua Fattal, and Sarah Shourd were hiking in the mountains of Iraqi Kurdistan when they unknowingly crossed into Iran and were captured by border patrol. Wrongly accused of espionage, the three Americans ultimately found themselves in Tehran’s infamous Evin Prison, where activists and protesters from the Green Movement were still being confined and tortured. Cut off from the world and trapped in a legal black hole, the three friends discovered that pooling their strength of will and relying on one another was the only way they could survive.   In A Sliver of Light , Bauer, Fattal, and Shourd finally get to tell their side of the story. They offer a rare glimpse inside Iran at a time when understanding this fractured state has never been more important. But beyond that, this memoir is a profoundly humane account of defiance, hope, and the elemental power of friendship—and a “ record of a human rights triumph” ( San Jose Mercury News ).